Opportunity cost for the digital dividend bandwidth: Application and comparison with LTE auctions outcomes - Nicola Garelli (International Telecommunications Society (ITS), 2014)
Radio spectrum represents a scarce resource assigned to operators by national regulatory authorities through auctions, beauty contests or other mechanisms, aimed at introducing sufficient incentives for an optimal use of such a resource. A prerequisite for designing efficient assignment methods is that regulatory agencies, which typically rely on incomplete and asymmetric information, clearly identify the expected value of the spectrum, to be used to set auction bases, prices in beauty contests and administered incentive prices. Those considerations are particularly actual since the transition to digital television transmission opened the space for reallocating parts of the spectrum, to increase its efficiency. The paper aims at refining a techno-analytical approach to estimate the value of spectrum portions, with a methodology based on opportunity-cost evaluation and at comparing the results with the outcomes of the recent LTE spectrum auctions. Research results could be used by regulatory agencies and by operators to better shape their approach to spectrum valuation.
Keywords: L51; L96; 330; Spectrum management; Digital Dividend; LTE; Opportunity cost; Investment